2018
DOI: 10.1002/tea.21470
|View full text |Cite
|
Sign up to set email alerts
|

Studying children's knowledge base of one‐sided levers as force amplifiers

Abstract: Attention to core concepts in science and engineering in early education has grown recently, and understanding levers as force amplifiers can be recognized as one of these. Previous studies focused on two‐sided levers and do not provide sufficient information about children's knowledge of levers as force amplifiers, nor about their learning and its support from an education perspective. It is important to consider load distance and force distance separately, as may be done in one‐sided levers, to understand ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 103 publications
(177 reference statements)
0
8
0
6
Order By: Relevance
“…Since mean scores do not necessarily express children's concepts, that is, having a correct, incorrect or no apparent understanding of TD and TS, we analyzed children's predictions for consistent response patterns using the binomial distribution with criterion <0.10 (Leuchter & Naber, 2018). With respect to TD, children had to make consistent predictions for 17 out of 26 predictions ( P 26;1/2 [ X = 17] = 8.43%), whereas for TS, the children had to make consistent predictions for 13 out of 26 predictions ( P 26;1/3 [ X = 17] = 5.40%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since mean scores do not necessarily express children's concepts, that is, having a correct, incorrect or no apparent understanding of TD and TS, we analyzed children's predictions for consistent response patterns using the binomial distribution with criterion <0.10 (Leuchter & Naber, 2018). With respect to TD, children had to make consistent predictions for 17 out of 26 predictions ( P 26;1/2 [ X = 17] = 8.43%), whereas for TS, the children had to make consistent predictions for 13 out of 26 predictions ( P 26;1/3 [ X = 17] = 5.40%).…”
Section: Resultsmentioning
confidence: 99%
“…With verbal scaffolds, the adult can help the children to rebuild the depicted gear configurations appropriately, thus enabling the children to observe TD and TS. The adult may ask questions to channel and focus children's attention on the relevant aspects of TD and TS and trigger cognitive processing (Chin, 2007; Hardy, Jonen, Möller, & Stern, 2006; Leuchter & Naber, 2018; Pea, 2004). An adult may also encourage comparisons to support the child in identifying relational similarities or differences between entities (Hsin & Wu, 2011; Richey & Nokes‐Malach, 2013).…”
Section: Guided Play As a Way To Foster Young Children's Learningmentioning
confidence: 99%
“…However, there are only a few studies that have deliberately compared the effectiveness of material scaffolds with additional verbal scaffolds for children’s science learning. Leuchter and Naber (2019) found that a combination of structured materials and verbal scaffolds supported 6- to 7-year-old children’s learning in the physics domain of force more than only materials, only verbal support or free exploration. Similarly, the results of Hadzigeorgiou (2002) show that 4- to 6-year-olds perform more meaningful activities at an inclined plane to explore the concept of mechanical stability when they received structured materials and verbal scaffolding compared to children who received only materials or played freely.…”
Section: Introduction: Science Educationmentioning
confidence: 95%
“…When encountering a new artifact, children have much to learn, including facts relevant to the whole artifact, such as its name and purpose, and facts about its components such as the role of specific parts in its operation. Mechanical machines provide a particularly unique learning challenge for young children, as they consist of not only external parts but also internal parts and mechanisms that are unseen but critical to their functioning (e.g., Leuchter and Naber, 2018;Reuter and Leuchter, 2020). Reflecting this fact, early childhood science curricula emphasize the importance of teaching young children about mechanical machines and forces during grade school (e.g., Ontario Ministry of Education, 2007;Michigan Department of Education, 2015).…”
Section: Introductionmentioning
confidence: 99%